Thermal and Electrical Study for PV Panel With Cooling - Z. Syafiqah; Y.M. Irwan; N.A.M. Amin; M. Irwanto; W.Z. Leow; A.R. Amelia (Indonesian Journal of Electrical Engineering and Computer Science, 2017)
Paper presents an investigation on photovoltaic (PV) panel with a direct-current (DC) fan cooling system. The DC fan cooling system was installed at the back of PV panel in order to reduce its operating temperature. The performance of PV panel can be affected with the increase of its operating temperature. Therefore, with the aid of the DC fan cooling system, it can enhance the performance by raise the output power generated. However, DC fan cooling system is considered as an active cooling system, whereby it consumes input power in operating it. The thermal behavior of PV panel with different DC fan speeds were observed by using a computational fluid dynamic (CFD) software. From the temperature obtained, a current-Voltage (I-V) and power-voltage (P-V) can be formed by using PSPICE due to examine its electrical performance. As the DC fan speed increases, the power input to operate it also increase. Hence, it is crucial to find the optimum speed so that the power generated by PV panel that can be saved is high.